Stable isotope analysis of upper Tithonian limestones with dinosaur footprints from Kirmenjak quarry (Istria, Croatia) - Cvetko Tešović, Blanka (Array, 2008)
Summary: The Kirmenjak locality of western Istria, Croatia, represents the oldest evidence of a dinosaur presence on the Adriatic-Dinaridic Carbonate Platform (ADCP). In a quarry at this locality, almost a thousand sauropod footprints are recognized in one distinctive trackbearing horizon within the Upper Tithonian limestones. The stable isotopes of oxygen and carbon, in conjunction with microfacies analysis of carbonate rocks exposed in this quarry, unravel details about the marginal marine or coastal environments in which sauropods left their footprints. Rocks from the trackbearing horizon, and laterally adjacent area, represent intertidal fenestral mudstones that form the top of a shallowing-upward succession, capped with a thin peloidal packstone/grainstone layer and overlain by subtidal mudstone. The formation and preservation of footprints was favoured by short-duration exposure of muddy sediment and its rapid burial beneath more mud. The isotopic composition of the sample from the trackbearing horizon is not substantially different from those of an adjacent area without footprints and from the overlying mudstone. Stable isotope analysis supports petrographic observations that the conditions on the carbonate tidal fl at during formation of rocks with dinosaur footprints were not unique. Documented variations in stable isotope compositions refl ect minor differences in the depositional and diagenetic history of the Kirmenjak quarry succession